Transmission system regularization with 5-level cascaded IPFC - Sridhar Babu Gurijala; K S Srikanth; Ramchandra Nittala; G. Rohit Reddy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
In recent years, there is an immensely huge demand to power due to industrialization and modernization, butcorrespondingly the amplification of generation and transmission has not been done due to constrained resources and environmental limitations. The huge growth in demand leads to various problems in power systems. Heavy growth in semiconductor technology made power electronics plays a key role in solving these problems. Flexible AC transmission system (FACTS) devices are used for fixing various problems in power system. They are used for enhancing the existing transmission capabilities and improving the system dynamic performance so that to make transmission system flexible and efficient in operation. Inter line power flow controller (IPFC) is a latest generation series connected FACTS device, having capability of controlling power flow among multi line in a transmission network. In this paper cascaded 5 level inverter is used as the inverter module for IPFC. Control techniques play a vital role in power flow control in the system, with the main objective of minimization of harmonics and obtaining a variable output with maximum fundamental component. This paper discusses various comparative case studies on IPFC with cascaded 5 level inverter using SPWM and SVM control techniques.